2020
DOI: 10.3390/pr8070803
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Solvent Extraction as a Green Tool for the Recovery of Polyphenols and Pigments from Wild Nettle Leaves

Abstract: This study aimed to investigate the performance of accelerated solvent extraction (ASE) as a green approach for the recovery of polyphenols and pigments from wild nettle leaves (NL). ASE was operated at different temperatures (20, 50, 80 and 110 °C), static times (5 and 10 min) and cycle numbers (1–4) using ethanol (96%) as an extraction solvent. In order to compare the efficiency of ASE, ultrasound assisted extraction (UAE) at 80 °C for 30 min was performed as a referent. Polyphenol and pigment analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 68 publications
(91 reference statements)
8
35
0
Order By: Relevance
“…Coumarins, isoflavones and other acids were present in lower concentrations: GM values 5.31, 3.09 and 2.88 mg 100 g −1 dm, respectively, while the least represented group of polyphenols were flavanones (GM 0.34 mg 100 g −1 dm). Moreover, obtained results are in accordance with the results of other authors [ 6 , 8 , 11 , 14 ], who reported quite similar phenolic profile in nettle extracts where cinnamic acids accounted for the most of presented total polyphenols.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Coumarins, isoflavones and other acids were present in lower concentrations: GM values 5.31, 3.09 and 2.88 mg 100 g −1 dm, respectively, while the least represented group of polyphenols were flavanones (GM 0.34 mg 100 g −1 dm). Moreover, obtained results are in accordance with the results of other authors [ 6 , 8 , 11 , 14 ], who reported quite similar phenolic profile in nettle extracts where cinnamic acids accounted for the most of presented total polyphenols.…”
Section: Resultssupporting
confidence: 92%
“…The presence of nettle natural color carriers, carotenoids and chlorophylls was monitored by HPLC analysis, which has detected a total of 13 carotenoids and 9 chlorophylls in wild nettle leaves and stalks, namely neoxanthin and its two derivatives, violaxanthin and its two derivatives, 13′- cis -lutein, lutein 5,6-epoxide, lutein, zeaxanthin, 9′- cis -lutein, α-carotene, β-carotene, chlorophyll a and its six derivatives and chlorophyll b and its derivative ( Figure 1 , Supplementary file 1 ). A similar chlorophylls and carotenoids composition was previously reported [ 4 , 11 ]. For statistical purposes, identified pigments were grouped and analyzed as total carotenoids and total chlorophylls, as well as their sum (total pigments) ( Table 4 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Since conventional extraction techniques have serious disadvantages, e.g., they are time-consuming, use large solvent amounts and consequently raising pollution issues, and finally do not results with the sufficient yield (Wang and Weller, 2006), novel extraction approaches are favored, among which accelerated solvent extraction (ASE) is one of the most promising. Through the combination of elevated temperature and pressure, shortening of the extraction time and lower solvent consumption, easy handling, being automated (Wang and Weller, 2006;Mottaleb and Sarker, 2012) and providing high extraction yields (Repajić et al, 2020), ASE manifests as very effective and environment-friendly technique. However, since the main challenge during extraction of target compounds is to achieve their highest yields, it is of a great importance to select the optimal extraction conditions.…”
Section: Introductionmentioning
confidence: 99%